Pengaruh Informasi Akuntansi, Profil Risiko Investor, dan Perilaku Investor Saham Individual Terhadap Keputusan Investasi Investor Mahasiswa di Universitas Islam Malang - Ainun Jariyah; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2023)
This study aims to analyze the influence of Accounting Information, Investor Risk Profile, and Individual Stock Investor Behavior on Investment Decisions of Student Investors at the Islamic University of Malang. This research was conducted using survey methods and data collection through questionnaires distributed to students as potential investors. Data analysis was performed using multiple linear regression techniques. The results of the study show that accounting information has a significant positive effect on investment decisions of student investors. This study also found that Investor Risk Profile has a significant positive influence on investment decisions of student investors. This shows that students tend to consider the level of risk they face in making investment decisions. Furthermore, this study also found that the behavior of individual stock investors has a significant positive influence on investment decisions of student investors.Keywords: Accounting information, investor risk profile, individual stock investor behavior.